Implementasi Algoritme Enkripsi Salsa20 untuk Pengamanan Data Video Surveilans secara Real-Time - Angger Ramadhan; Ari Kusyanti; Primantara Hari Trisnawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Video Video surveillance is a form of surveillance for actions that may violate the law in the form of a collection of frames sent in real-time from a device that has a camera to another device that is tasked with conducting surveillance. However, problems can occur when the frame sent is taken by an unauthorized party, so that it can interfere with the confidentiality of the frame data. In previous research, there is a method for securing these frames, namely in the form of encryption using a block cipher algorithm and not using a stream cipher algorithm. Therefore, in this study, the implementation of the stream cipher algorithm, namely Salsa20, was implemented. Implementation of Salsa20 is applied to systems with client-server network architecture, namely encryption on the server and decryption on the client. After that, tests are carried out related to test vectors, performance, and attacks. The results of the test vector test have been successful because the output from the system is the same as the output on the paper. Furthermore, for the results of the attack test, the sniffing test succeeded in getting the frame on the network but could not get the information because the frame was encrypted and the ciphertext-only attack test failed because it had not succeeded in getting the key or plaintext.